KOMPETENSI GURU PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN DALAM PELAKSANAAN EVALUASI PEMBELAJARAN DAN IMPLIKASINYA TERHADAP KETERCAPAIAN KOMPETENSI SISWA (STUDI DI SMP NEGERI 15 SURAKARTA) - Kowidito, Danau Asa (Educitizen, 2013)
The purpose of this study is to: (1). know teachers understanding and ability to perform as well as selecting an assessment tool Pancasila and Citizenship Education in the cognitive and affective aspects, (2). know any constraints experienced teachers in assessing student learning outcomes in subjects Pancasila and Citizenship Education on the cognitive and affective aspects, and (3). determine impact experienced by teachers in assessing learning outcomes in subjects Pancasila and Citizenship Education on the cognitive and affective aspects. This research is a qualitative descriptive study. The research strategy is a single strategy rooted. The data source is the informant, events or activities and documents. The sampling technique was purposive sampling. Data collection techniques were interviews, observation and document analysis. Researchers used a triangulation of data and methods. Data analysis techniques using an interactive model. Research procedure: preparation, data collection, data analysis, and preparation of research reports.Based on these results it can be concluded: (1). Pancasila and Citizenship Education learning outcomes assessment performed by Junior High School Civics teacher 15 Surakarta was appropriate but not maximized, because the matter has not been developed into various forms of matter. (2). Constraints faced Pancasila and Citizenship Education teachers in assessing student learning outcomes in the cognitive aspects in the implementation of daily tests can not be done entirely in accordance with the time schedule or because of the time that has been prepared absorbed in learning activities. Constraints faced Pancasila and Citizenship Education teachers in assessing student learning outcomes in the affective aspect is that the check list does not directly provide the value or score. (3). The positive impact of the use of tests in the cognitive assessment was not too difficult for the teacher arranged the matter. However, there is a negative impact, among others: (a) very limited test sample (b) are highly subjective (c) the test is usually less reliable. The use of non-test assessment tool to positively impact the affective aspect to know the talents and interests of learners. The negative impact of the use of the test is a check list of affective indirect giving a score or value because of its reliability is questionable.